(untitled) (Biological Sciences - PJSIR, 2020)
The present study investigates the phyto-accumulation capacity of two cultivars of sunflower (Helianthus annuus L.) for heavy metals. Analysis of the data recorded ten weeks after sowing indicated that heavy metal application had significantly (p<0.05) affected all the parameters under study. Interaction of EDTA x cultivar and EDTA x cultivar x heavy metal had significantly (p<0.05) affected root fresh weight, root dry weight and heavy metal accumulation. EDTA application had significant (p<0.05) effect on heavy metal accumulation when data was noted ten weeks after sowing. The data also revealed that maximum plant height, number of leaves/plant, shoot fresh weight and dry weight, root fresh and dry weight was noted in control pots (0 mg/kg heavy metal). The suggested that maximum shoot fresh weight shoot dry weight, root fresh weight and root dry weight was noted in pots kept at control with San Sun-33 when applied with 5 mM EDTA. Similarly, maximum heavy metal accumulation was recorded in treatment sown of HiSun-33 applied with 5 mM EDTA and 50 mM chromium. Maximum root fresh weight was noted in control pots treated with 5 mM EDTA and planted with San Sun-33. Similarly, heavy metal accumulation was more in HiSun-33 treated with 50 mg/kg chromium and 5 mM EDTA. In terms of accumulation of heavy metals, HiSun-33 demonstrated better accumulation of the tested heavy metals then SanSun-33, anyhow the growth of SanSun-33 was better than HiSun-33 due to lesser accumulation of heavy metals.